2008
DOI: 10.1007/s12035-008-8042-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Stress-Induced Reproductive Dysfunction in Female Macaques

Abstract: It is now well accepted that stress can precipitate mental and physical illness. However, it is becoming clear that given the same stress, some individuals are very vulnerable and will succumb to illness while others are more resilient and cope effectively, rather than becoming ill. This difference between individuals is called stress sensitivity. Stress-sensitivity of an individual appears to be influenced by genetically inherited factors, early life (even prenatal) stress, and by the presence or absence of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 219 publications
(250 reference statements)
6
80
1
1
Order By: Relevance
“…SS monkeys have suppressed physiological release of serotonin (6), fewer serotonergic cells, and low expression of a number of genes in the serotonin pathway, including FEV1, TPH2, SERT, MAO-A, and MAO-B, in the dorsal raphe nucleus (5,7). Moreover, treatment with a selective serotonin reuptake inhibitor, citalopram, increases ovarian steroid hormone secretion in SS monkeys (14).…”
Section: Discussionmentioning
confidence: 99%
“…SS monkeys have suppressed physiological release of serotonin (6), fewer serotonergic cells, and low expression of a number of genes in the serotonin pathway, including FEV1, TPH2, SERT, MAO-A, and MAO-B, in the dorsal raphe nucleus (5,7). Moreover, treatment with a selective serotonin reuptake inhibitor, citalopram, increases ovarian steroid hormone secretion in SS monkeys (14).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that stress factors have an inhibitory impact on the neuroendocrine regulation of reproduction in women (Warren and Fried, 2001 ) as in adult nonhuman female primates (Bethea et al, 2008). Strenuous physical exercise, emotional stress or weight loss are associated with hypothalamic amenorrhea (Warren and Fried, 2001 ;Bethea et al, 2008).…”
Section: Critical Windows Of Exposure To Stress and Timing Of Pubertymentioning
confidence: 99%
“…Strenuous physical exercise, emotional stress or weight loss are associated with hypothalamic amenorrhea (Warren and Fried, 2001 ;Bethea et al, 2008). The impact of stress on timing of puberty is particularly complex to study.…”
Section: Critical Windows Of Exposure To Stress and Timing Of Pubertymentioning
confidence: 99%
“…SS animals chronically have a lower release of serotonin (5-HT) in response to fenfluramine [6], and have a downregulation of the central serotonergic system, as indicated by significantly less tryptophan hydroxylase 2 (TPH2) expression [9], less serotonin reuptake transporter (SERT) gene expression, less 5-HT 1A receptor gene expression and less expression of the genes that degrade serotonin (MAO-A and MAO-B) in the raphe nucleus [7,10]. In the hypothalamus, there is an upregulation of 5-HT 2A and 5-HT 2C receptors [11], and an increase in GAD67 gene expression [11], which are inhibitory to the reproductive axis.…”
Section: Introductionmentioning
confidence: 99%
“…In the hypothalamus, there is an upregulation of 5-HT 2A and 5-HT 2C receptors [11], and an increase in GAD67 gene expression [11], which are inhibitory to the reproductive axis. We also found that SS animals have less immunoreactive gonadotropin-releasing hormone (GnRH) in the median eminence, lower pituitary luteinizing hormone and follicle-stimulating hormone secretion, and lower ovarian estradiol and progesterone secretion compared to more stress-resilient monkeys, even when they are not experiencing stress [10,12]. …”
Section: Introductionmentioning
confidence: 99%